Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
Cochrane Database of Systematic Reviews 2010
DOI: 10.1002/14651858.cd006942.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Synchronised approach for intrauterine insemination in subfertile couples.

Abstract: There is no evidence to advise one particular treatment option over another. The choice should be based on hospital facilities, convenience for the patient, medical staff, costs and drop-out levels. Since different time intervals between hCG and IUI did not result in different pregnancy rates, a more flexible approach might be allowed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(16 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…Intrauterine insemination (IUI) is a commonly used infertility treatment option for couples with unexplained subfertility, low-grade endometriosis, impotentia coeundi and sexual function disorders, as well as male subfertility [1]. The probability of conceiving with this infertility treatment depends on several factors, including age, reason for subfertility or infertility, absence/presence and type of ovarian stimulation, as well as the timing of insemination [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intrauterine insemination (IUI) is a commonly used infertility treatment option for couples with unexplained subfertility, low-grade endometriosis, impotentia coeundi and sexual function disorders, as well as male subfertility [1]. The probability of conceiving with this infertility treatment depends on several factors, including age, reason for subfertility or infertility, absence/presence and type of ovarian stimulation, as well as the timing of insemination [2].…”
Section: Introductionmentioning
confidence: 99%
“…Usually, IUI is performed around ovulation and, as the fertile timeframe is limited, the correct timing of the insemination seems to be important. However, the quality of evidence to determine the potential difference in effectiveness between different methods of synchronization of ovulation and insemination is low [1, 4, 5]. …”
Section: Introductionmentioning
confidence: 99%
“…The mechanisms by which inhibin antagonizes activin actions are not fully understood. It has been shown that inhibin is capable of binding to type II activin and BMP receptors through its b (beta) subunit and preventing the recruitment of type I receptor, thus antagonizing the actions of activins [ 218 ] . This may be one of the mechanisms by which inhibins antagonize activin actions.…”
Section: Mechanism Of Action Of Activins Inhibins Follistatin and Amhmentioning
confidence: 99%
“…The Cochrane review by Cantineau et al (2010), found no significant difference between different timing methods for IUI expressed as live birth rates, although the group sizes were small [hCG versus LH surge (OR: 1.0, 95% CI, 0.06-18)]. This review was also in agreement with the meta-analysis by Kosmas et al (2007), which showed that urinary LH surge detection remains as effective as hCG administration as a method for IUI timing in clomiphene citrate-IUI treatment (OR for pregnancy: 0.66, 95% CI, 0.35-1.21) in the subgroup with male infertility.…”
Section: Timing Of Inseminationmentioning
confidence: 99%
“…The updated Cochrane review (Cantineau et al, 2010) revealed that based on the results of five studies reporting pregnancy rate per couple in stimulated IUI cycles, double IUI resulted in more pregnancies than single IUI (Peto OR: 1.8; 95% CI, 1.4-2.4). There were no data for live birth per couple or ongoing pregnancies.…”
Section: Single Versus Double Inseminationmentioning
confidence: 99%